The Adaptation of a Clinic-Adjacent Parking Garage for Drive-In COVID-19 Vaccination. (September 2021) - Reise, Rachel; Huang, Yushi; Usmani, Silken A; Gruber, Laura; Patel, Natasha; Green, Tracy; Swilley, Lindsay; Dewar, Marvin A; Gums, John
Purpose: The distribution and vaccination of COVID-19 vaccines to billions of people worldwide will likely be one of the biggest public health undertakings in history. There has been a large focus on identifying processes to safely, efficiently, and effectively vaccinate large populations. We aimed to describe the development and operationalization of a drive-in COVID-19 vaccine site in a parking garage adjacent to outpatient clinics at University of Florida (UF) Health Physicians and how it was informed by the roll-out of SARS-CoV-2 testing and administration of respiratory vaccinations. Design/Methodology/Approach: A technical description and analysis of a drive-in COVID-19 vaccine site. Findings: We incrementally increased the number of vaccines performed per day from 300 in the first 2 weeks to 700 an additional 2 weeks later. By the end of January, we completed nearly 14 000 vaccinations. At this capacity, we estimate the site could performed 5000 vaccinations per week. Practical Implications: This manuscript provides step-by-step guidance how to develop, operationalize, and implement a sustainable drive-in COVID-19 vaccination site. Originality/Value: To our knowledge, this is the first description of a drive-in approach to COVID-19 vaccination. Our findings can help inform other health entities as they develop or expand vaccination efforts that may serve as a template for other sites to adapt.